Zinc in the ruminant nutrition (Veterinary Science, 2017)
This review summarizes the literature on the zinc functions and metabolism in the mammals, the clinical and biochemical characteristics of this mineral deficiency and the diagnostic tools to detect them, specially in the case of marginal or subclinical deficiencies. Finally, some aspects of practical nutrition relevance are reviewed, with particular reference to ruminants
Keywords: Zinc; Ruminant nutrition; Metabolism